Redesain tata letak fasilitas dengan pendekatan systematic layout planning di UD. manjur makmur - Wahyu Kanti Dwi; Dian Setiya Widodo; Supardi Supardi (AGROINTEK, 2022)
Facility layout design is important in companies to increase capacity and productivity. UD. Manjur Makmur is a privately owned trading business located in Lumajang Regency. UD. Manjur Makmur's product is noni juice. The current layout of the company is not optimal, marked by the placement of each production room that is not in accordance with the production flow. This causes alternating current and causes cross-contamination with the surrounding environment. The purpose of this study is to develop recommendations for layouts at UD.Manjur Makmur; and analysis of layout recommendations to increase profits and minimize OMH by using the SLP (Systematic Layout Planning) method. The method used to design the layout of the facility is the SLP (Systematic Layout Planning) method. The research was conducted at UD. Manjur Makmur and the Laboratory of Agroindustry Untag Surabaya. The results of the study obtained that the material handling costs in the proposed design were Rp118,000 compared to the current design of Rp1,192,133. so that the recommendation for the new facility layout design can reduce the distance traveled from 40073.55 meters to 23.6 meters which will also have an impact on expenses.